The Role of Cognitive Development and Strategic Task Tendencies in the Bilingual Advantage Controversy - Struys, Esli; Duyck, Wouter; Woumans, Evy (Frontiers in Psychology, 2018)
Recent meta-analyses have indicated that the bilingual advantage in cognitive control is not clear-cut. So far, the literature has mainly focussed on behavioural differences and potential differences in strategic task tendencies between monolinguals and bilinguals have been left unexplored. In the present study, two groups of younger and older bilingual Dutch-French children were compared to monolingual controls on a Simon and flanker task. Beside the classical between-group comparison, we also investigated potential differences in strategy choices as indexed by the speed-accuracy trade-off. Whereas we did not find any evidence for an advantage for bilingual over monolingual children, only the bilinguals showed a significant speed-accuracy trade-off across tasks and age groups. Furthermore, in the younger bilingual group, the trade-off effect was only found in the Simon and not the flanker task. These findings suggest that differences in strategy choices can mask variations in performance between bilinguals and monolinguals, and therefore also provide inconsistent findings on the bilingual cognitive control advantage.